A Phase II study of the safety and efficacy of lenvatinib in patients with advanced thyroid cancer. (14th January 2019) - Takahashi, Shunji; Kiyota, Naomi; Yamazaki, Tomoko; Chayahara, Naoko; Nakano, Kenji; Inagaki, Lina; Toda, Kazuhisa; Enokida, Tomohiro; Minami, Hironobu; Imamura, Yoshinori; Fukuda, Naoki; Sasaki, Tatsuya; et al.
Aim: To investigate the safety and efficacy of lenvatinib in advanced thyroid cancer.Patients/methods: In this Phase II study, 51 Japanese patients with radioiodine-refractory differentiated thyroid cancer (RR-DTC), medullary thyroid cancer (MTC) or anaplastic thyroid cancer (ATC) received once-daily lenvatinib 24 mg. The primary end point was safety.Results: All patients experienced ≥1 adverse event (AE); only one patient experienced an AE leading to discontinuation. The most common any-grade AEs were hypertension, decreased appetite, palmar-plantar erythrodysesthesia, fatigue and proteinuria. Response rates for RR-DTC: 68%; MTC: 22%; ATC: 24%. Median progression-free survival for RR-DTC: 25.8 months; MTC: 9.2 months; ATC: 7.4 months.Conclusion: Lenvatinib demonstrated a manageable safety profile, proven antitumor activity in RR-DTC and promising efficacy in MTC and ATC. Clinical trial registration: clinicaltrials.gov NCT01728623 Lay abstract: Lenvatinib is approved in Japan and elsewhere to treat radioiodine-refractory differentiated thyroid cancer; however, new therapies are also needed for other forms of advanced thyroid cancer (such as medullary thyroid cancer and anaplastic thyroid cancer). Fifty-one patients from Japan with advanced thyroid cancer received lenvatinib in this clinical trial. All patients experienced at least one side effect during treatment but only one patient experienced a side effect that necessitated stopping lenvatinib therapy. In general, patients tolerated lenvatinib treatment because the side effects were manageable. Lenvatinib treatment showed promising antitumor effects for patients across all thyroid cancer subtypes tested.